2010
DOI: 10.3109/08037051.2010.488053
|View full text |Cite
|
Sign up to set email alerts
|

Local heat stress and skin blood flowmotion in subjects with familial predisposition or newly diagnosed hypertension

Abstract: Skin microcirculation response to local heat stress is altered in hypertensive patients with decrease in maximal heat CVC values. Moreover, normotensive subjects with familial predisposition to hypertension are characterized by diminished myogenic origin of skin blood flowmotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Sheppard et al [34] using wavelet based analysis similarly reported a decrease in the myogenic band in the hand during warming, as did Gryglewska et al [35] using a Fast Fourier Transform (FFT). However, Hodges et al [36] also using FFT reported warming-induced increases in the three LF bands at both the forearm and the leg in young healthy individuals.…”
Section: B Power-frequency Profiles In Low Vs High Flow Statesmentioning
confidence: 92%
See 2 more Smart Citations
“…Sheppard et al [34] using wavelet based analysis similarly reported a decrease in the myogenic band in the hand during warming, as did Gryglewska et al [35] using a Fast Fourier Transform (FFT). However, Hodges et al [36] also using FFT reported warming-induced increases in the three LF bands at both the forearm and the leg in young healthy individuals.…”
Section: B Power-frequency Profiles In Low Vs High Flow Statesmentioning
confidence: 92%
“…Greater variability may also indicate an ability to influence flow independently of the spectral amplitude of flowmotion [16]. Thus a declining spontaneous variation in flowmotion activity as seen in vascular beds at risk of CV and Met disease [14] may contribute to a loss of system flexibility and adaptability in the face of physiological or pathological challenge.…”
Section: Complexity Of Network Perfusion and Oxygenation In Low Vsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normotensive men with a positive family history of hypertension showed an increased diastolic blood pressure after isometric handgrip testing when compared to controls without a family history of hypertension (Widgren et al, 1992). Similarly, the microcirculation response to local heat stress and skin blood flow is altered in normotensive with family history of hypertension (Gryglewska et al, 2010). In a cohort of adults and their children followed for six years, this increased response to stress was the strongest in the subjects found to display the highest diastolic and systolic blood pressure six years later.…”
Section: Enhanced Stress Response Is Predictive Of Hypertension -Concmentioning
confidence: 95%
“…These periodic oscillations, or skin flowmotion, represent the influence of heart beat (0.6–2.0Hz), respiration (0.15–0.6Hz), myogenic (~0.05–0.15Hz) (Stefanovska et al, 1999), neurogenic (~0.02–0.05Hz) (Kastrup et al, 1989; Soderstrom et al, 2003), and endothelial (~0.0095–0.02Hz) influences on vascular smooth muscle relaxation (Gustafsson et al, 1993; Kvandal et al, 2003; Kvernmo et al, 1999; Rossi et al, 2008a). Spectral analysis has been performed on populations with known microvascular dysfunction such as peripheral arterial obstructive disease (Rossi et al, 2005), chronic kidney disease (Rossi et al, 2008b), diabetes (Schmiedel et al, 2007), chronic smokers (Avery et al, 2009; Rossi et al, 2007), hypercholesterolemics (Rossi et al, 2009) and essential hypertensive men and women (Gryglewska et al, 2010a; Gryglewska et al, 2010b; Rossi et al, 2006). While these studies observed altered skin flowmotion responses, many of them utilized different skin vasoreactivity tests and subject populations in which the mechanisms mediating skin blood flow are not thoroughly understood.…”
Section: Introductionmentioning
confidence: 99%